2001
DOI: 10.1063/1.1360217
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrostatic pressure on degradation of CdTe/CdMgTe heterostructures grown by molecular beam epitaxy on GaAs substrates

Abstract: We have shown that external hydrostatic pressure leads to the creation of structural defects, mainly in the vicinity of the II-VI/GaAs interface in the CdTe/Cd 1-x Mg x Te heterostructures grown by the molecular beam epitaxy method on GaAs substrates.These defects propagating across the epilayer cause permanent damage to the samples from the point of view of their electrical properties. In contrast, photoluminescence spectra are only weakly influenced by pressure. Our results shed light on the degradation proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A significant difference in thermal expansion coefficients caused lattice deformation or dislocations that led to microcracks during cooling from a high growth temperature . Likewise, external hydrostatic pressure can increase the residual internal stress due to mismatch in the compressibility between the film and the substrate. , Interdiffusion of ions can also result in the crystal defects. , …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A significant difference in thermal expansion coefficients caused lattice deformation or dislocations that led to microcracks during cooling from a high growth temperature . Likewise, external hydrostatic pressure can increase the residual internal stress due to mismatch in the compressibility between the film and the substrate. , Interdiffusion of ions can also result in the crystal defects. , …”
mentioning
confidence: 99%
“…9 Likewise, external hydrostatic pressure can increase the residual internal stress due to mismatch in the compressibility between the film and the substrate. 10,11 Interdiffusion of ions can also result in the crystal defects. 12,13 As compared to the generation of defects in thin films, the generation of defects in coreϪshell nanostructured materials has been rarely investigated.…”
mentioning
confidence: 99%
“…For example, in modulation-doped GaInAs/AlInAs and CdTe/CdMnTe heterostructures [1,2] large parallel conduction often prevents the observation of the quantum Hall effect (QHE) and makes the characterization of two-dimensional electron gas (2DEG) very difficult. In our previous papers [3,4] we have shown that also in the CdTe/Cd 1--x Mg x Te single quantum well heterostructures the parallel transport often occurs in spite of high material quality. The elimination of this phenomenon in low-dimensional II-VI structures is necessary for their possible application in light emitting devices or in hybrid optoelectronics as spin injectors.…”
mentioning
confidence: 99%